Skip to main content

Binomial Identities

The Binomial Theorem

Theorem I

For all nonnegative integers nn,

(x+y)n=k=0n(nk)xkynk.(x+y)^n=\sum_{k=0}^n\left(\begin{array}{l} n \\ k \end{array}\right) x^k y^{n-k} .

Proof

Consider the product of nn sums, (x+y)(x+y)(x+y)(x+y)(x+y) \cdots(x+y). When computing this product, we take one summand from each parentheses, multiply them together, then repeat this in all of 2n2^n possible ways and add the results. We get a product equal to xkynkx^k y^{n-k} each time we take kk summands equal to xx. There are (nk)k\left(\begin{array}{l}n \\ k\end{array}\right) k-element subsets of the set of all nn parentheses, so we will get such a term (nk)\left(\begin{array}{l}n \\ k\end{array}\right) times, and the proof is complete.

Theorem II

For all positive integers nn, the alternating sum of binomial coefficients (nk)\left(\begin{array}{l}n \\ k\end{array}\right) is zero. In other words,

k=0n(1)k(nk)=0\sum_{k=0}^n(-1)^k \cdot\left(\begin{array}{l} n \\ k \end{array}\right)=0

Proof

Applying the binomial theorem with x=1x=-1 and y=1y=1 we immediately get our claim.

Theorem III

For all nonnegative integers nn and kk, the identity

(nk)+(nk+1)=(n+1k+1)\left(\begin{array}{l} n \\ k \end{array}\right)+\left(\begin{array}{c} n \\ k+1 \end{array}\right)=\left(\begin{array}{l} n+1 \\ k+1 \end{array}\right)

holds.

Proof

The right-hand side is, by definition, the number of k+1k+1-element subsets of [n+1][n+1]. Such a subset SS either contains the element n+1n+1, or it does not. If it does, then the rest of SS is a kk-element subset of [n][n], and these are enumerated by the first member of the left-hand side. If it does not, then SS is a k+1k+1-element subset of [n][n], and these are enumerated by the second member of the left-hand side.

Theorem IV

For all nonnegative integers n,

2n=k=0n(nk)2^n=\sum_{k=0}^n\left(\begin{array}{l} n \\ k \end{array}\right)

Proof I

Both sides count the number of all subsets of an nn-element set. The left-hand side counts directly, while the right-hand side counts the number of kk-element subsets, then sums over kk.

Proof II

Apply the binomial theorem with x=y=1x=y=1.

Theorem V

For all nonnegative integers kk and nn,

(kk)+(k+1k)+(k+2k)++(nk)=(n+1k+1).\left(\begin{array}{l} k \\ k \end{array}\right)+\left(\begin{array}{c} k+1 \\ k \end{array}\right)+\left(\begin{array}{c} k+2 \\ k \end{array}\right)+\cdots+\left(\begin{array}{l} n \\ k \end{array}\right)=\left(\begin{array}{l} n+1 \\ k+1 \end{array}\right) .

Proof

The right-hand side clearly counts all k+1k+1-element subsets of [n+1][n+1]. The left-hand side counts the same, separated into cases according to the largest element. That is, there are (kk)\left(\begin{array}{l}k \\ k\end{array}\right) subsets of [n+1][n+1] that have k+1k+1 elements whose largest element is k+1k+1; there are (k+1k)\left(\begin{array}{c}k+1 \\ k\end{array}\right) subsets of [n+1][n+1] that have k+1k+1 elements whose largest element is k+2k+2, and so on. In general, there are (k+ik)\left(\begin{array}{c}k+i \\ k\end{array}\right) subsets of [n+1][n+1] that have k+1k+1 elements whose largest element is k+i+1k+i+1, for all inki \leq n-k. Indeed, if the largest element of such a subset is k+i+1k+i+1, then its remaining kk elements must form a subset of [k+i][k+i].

Theorem VI

For all nonnegative integers nn, the identity

k=1nk(nk)=n2n1\sum_{k=1}^n k\left(\begin{array}{l} n \\ k \end{array}\right)=n 2^{n-1}

holds. Before proving the theorem, note that it is not even obvious why

k=1nk(nk)2n1\frac{\sum_{k=1}^n k\left(\begin{array}{l} n \\ k \end{array}\right)}{2^{n-1}}

should be an integer. Our proof will show that it is not only an integer, it is equal to nn. This hopefully convinces the reader that binomial coefficient identities are beautiful.

Proof I

Both sides count the number of ways to choose a committee among nn people, then to choose a president from the committee. On the left-hand side, we first choose a kk-member committee in (nk)\left(\begin{array}{l}n \\ k\end{array}\right) ways, then we choose its president in kk ways. On the right-hand side, we first choose the president in nn ways, then we choose a subset of the remaining (n1)(n-1)-member set of people for the role of non-president committee members in 2n12^{n-1} ways.

We provide another proof that uses the binomial theorem. It also gives us an early hint that sometimes very finite-looking problems, such as choice problems, can be solved by using methods from infinite calculus, such as functions and their derivatives.

Proof II

Apply the binomial theorem with y=1y=1 to get the identity

(x+1)n=k=0n(nk)xk.(x+1)^n=\sum_{k=0}^n\left(\begin{array}{l} n \\ k \end{array}\right) x^k .

Both sides are differentiable functions of the variable xx. So we can take their derivatives with respect to xx, and they must be equal. This yields

n(x+1)n1=k=1nk(nk)xk1.n(x+1)^{n-1}=\sum_{k=1}^n k \cdot\left(\begin{array}{l} n \\ k \end{array}\right) x^{k-1} .

Now substitute x=1x=1.

Theorem VII (Vandermonde's identity)

For all positive integers nn, mm, and kk,

(n+mk)=i=0k(ni)(mki).\left(\begin{array}{c} n+m \\ k \end{array}\right)=\sum_{i=0}^k\left(\begin{array}{c} n \\ i \end{array}\right)\left(\begin{array}{c} m \\ k-i \end{array}\right) .

Proof

The left-hand side counts all kk-element subsets of [n+m][n+m]. The right-hand side counts the same, according to the number of elements chosen from [n][n]. Indeed, we can first choose ii elements from [n][n] in (ni)\left(\begin{array}{l}n \\ i\end{array}\right) ways, then choose the remaining kik-i elements from the set {n+1,n+2,,n+m}\{n+1, n+2, \cdots, n+m\} in (mki)\left(\begin{array}{c}m \\ k-i\end{array}\right) ways.

The Multinomial Theorem

Definition

Let n=i=1kain=\sum_{i=1}^k a_i, where nn and a1,a2,,aka_1, a_2, \cdots, a_k are nonnegative integers. We define

(na1,a2,,ak)=n!a1!a2!ak!.\left(\begin{array}{c} n \\ a_1, a_2, \cdots, a_k \end{array}\right)=\frac{n !}{a_{1} ! \cdot a_{2} ! \cdots a_{k} !} .

The numbers (na1,a2,,ak)\left(\begin{array}{c}n \\ a_1, a_2, \cdots, a_k\end{array}\right) are called multinomial coefficients.

Theorem I (Multinomial theorem)

For all nonnegative integers nn and kk, the equality

(x1+x2++xk)n=a1,a2,,ak(na1,a2,,ak)x1a1x2a2xkak\left(x_1+x_2+\cdots+x_k\right)^n=\sum_{a_1, a_2, \cdots, a_k}\left(\begin{array}{c} n \\ a_1, a_2, \cdots, a_k \end{array}\right) x_1^{a_1} x_2^{a_2} \cdots x_k^{a_k}

holds. Here the sum is taken over all kk-tuples of nonnegative integers a1,a2,,aka_1, a_2, \cdots, a_k such that n=i=1kain=\sum_{i=1}^k a_i

Proof

We have to show that the term x1a1x2a2xkakx_1^{a_1} x_2^{a_2} \cdots x_k^{a_k} can be obtained in exactly (na1,a2,,ak)\left(\begin{array}{c}n \\ a_1, a_2, \cdots, a_k\end{array}\right) ways as a product of kk variables, one from each parentheses of (x1+x2++xk)(x1+x2++xk)\left(x_1+x_2+\cdots+x_k\right) \cdots\left(x_1+x_2+\cdots+x_k\right). To obtain such a term, we have to choose xix_i from exactly ii parentheses, for all i[k]i \in[k].

Now let us take aia_i copies of xix_i, for all i[k]i \in[k], and order these nn letters linearly. Theorem 3.53.5 shows that this can be done in exactly (na1,a2,,ak)\left(\begin{array}{c}n \\ a_1, a_2, \cdots, a_k\end{array}\right) ways. On the other hand, each linear ordering pp defines a natural way of choosing variables from the parentheses. Indeed, if the jj th letter of pp is xix_i, then from the jj th parentheses, we choose xix_i. This way our (na1,a2,,ak)\left(\begin{array}{c}n \\ a_1, a_2, \cdots, a_k\end{array}\right) linear orderings will produce exactly (na1,a2,,ak)\left(\begin{array}{c}n \\ a_1, a_2, \cdots, a_k\end{array}\right) terms that are equal to x1a1x2a2xkakx_1^{a_1} x_2^{a_2} \cdots x_k^{a_k}.

It is clear that this procedure establishes a bijection from the set of linear orderings of nn letters, aia_i of which is equal to xix_i for all i[k]i \in[k] onto that of terms of (x1+x2++xk)n\left(x_1+x_2+\cdots+x_k\right)^n that are equal to x1a1x2a2xkakx_1^{a_1} x_2^{a_2} \cdots x_k^{a_k}. Therefore, the coefficient of x1a1x2a2xkakx_1^{a_1} x_2^{a_2} \cdots x_k^{a_k} in (x1+x2++xk)n\left(x_1+x_2+\cdots+x_k\right)^n is precisely (na1,a2,,ak)\left(\begin{array}{c}n \\ a_1, a_2, \cdots, a_k\end{array}\right), and the proof follows.